The contractors’ attributes for the construction project success / Mohd Hafiz Saberi ... [et al.] - Mohd Hafiz, Saberi; Norbaizura, Abu Bakar; Norhafizah, Yusop; Suhaila Ali, Ali; Mohd Fisal, Ishak; Farhan, Md Dahlan; Noraini, Abdul Rani (2015)
The important contractor attributes for the construction project success are one of the main critical issues in the construction project. The contractor has challenges in term of additional knowledge and skills in order to achieve the successful project. The aim of this research is to identify the contractors’ attributes for the construction project success. The objective that has been established to achieve the aim of the study is to determine the important contractor attributes for the construction project success. The descriptive data obtained through questionnaire of 33 respondents from Project Manager, Engineer, Site Supervisor and Technical Assistant that employed with contractor G7. The data gathered was analysed using Statistic Package for Social Science (SPSS). There were adopted the analysis descriptive statistics technique using score mean and percentage. The result of this study indicated that the important attributes for the construction project success are financial, management or technical, past experience, past performance, health and safety, quality and resources attributes. The finding of this study can give a guideline to contractor to improve their attributes in order to achieve the successful project.